The return of a queen - Lenhard, Elizabeth (Volo : Hyperion Books for Children New York, 2004)
The rebel forces in Metamoor have been shattered by Caleb's transformation and Phobos has grown more desperate to take over the throne and destroy his sister. When the final battle is over, a new queen will reign